Analisis Variabel yang Berpengaruh terhadap Pengembangan Industri Kecil - Daud Pulo Mangesa (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
Corporate world and businessmen face the open challenge since free market of ASEAN 2003 and free market of ASIA 2020 take-place. It claim corporate world and businessmen to improving their competitiveness in order to become best and strongest. Since Indonesia faced multidimensi crisis in 1997, the economics of Indonesia is not convalesce fully. The most impact felt is workers retired, especially at big scale company, but it didn't happen at small scale company because small industry has important role to take care of growth dynamics and extension of society economics. The target of this research were: 1) To know any kind of variables that induce the development of small industry of traditional cloth weave in Raba Dompu Sub-Province of Bima, and (2) To know which variable that giving biggest influence to development of it. This Research is a survey research and use Quisioner. Goals population in this research is all entrepreneur weave traditional cloth in Raba Dompu Sub-Province of Bima. It counted 96 people. There 9 variables in this research, that are: independent variable (free variable) include: raw material (X1), labour (X2), machine (X3), capital (X4), product (X5). price (X6), distribution channel (X7), promotion (X8) and emulation intensity (X9). While dependent variable (Y) is industry development. Result of Test Validity and Reliabilitas indicated that all variable (27 variables) is valid and reliable. They can become an input for factor analysis. From these factor, writer get 9 new variable (factor), they were: 1) economic Age of machine, 2) weave cloth brand, 3) employees office hours, 4) amenity market cloth, 5) time for processing raw material, 6) mount emulation of price with competitor, 7) amenity get working capital, 8) duration acceptance of raw material and 9) yielded weave product. Base to the Doubled Linear regression Analysis, we can know that ninth of the factor have an effect to development of small industry of cloth weave of tradisioanl in Raba Dompu Sub-Province of Bima. And level of influence of these factors are equal to 75,4%, while the rest (24,6%) is explained by other factor which do not packed into the model.